Hydrodynamic behavior and start-up performance of a periodic anaerobic baffled reactor in an “every second” switching manner treating traditional Chinese medicine wastewater - Liu, Xiaolei; Yuan, Yixing; Ren, Nanqi (Frontiers in Microbiology, 2023)
Most studies focus on the 'clockwise sequential' switching manner for a fourcompartment periodic anaerobic baffled reactor (PABR), while the exploration of the 'every second' option on the feasibility for real industrial wastewater treatment is rare reported. Hence, a PABR treating traditional Chinese medicine wastewater was run continuously in 'every second' switching manner with both switching period T and hydraulic residence time of 48 h. Satisfactory start-up performance was achieved during the operation of a climbing average organic load rate at about 1, 2, 4 and 6 kg COD m -3 d -1 for 12, 24, 24 and 6 d, respectively. The average COD removal were 87.20% after the second lifting of OLR and 89.98% after the third one. Denaturing gradient gel electrophoresis and its cluster analysis showed the microbial communities in each compartment adapted their structure in response to the periodically changing microecology conditions. Moreover, residence time distribution test with tap water in the clean PABR was carried out in experiments and in computational fluid dynamics (CFD) simulations, both of which were in good agreement. The CFD model output visualized flow velocity field and hydrodynamic-mass transport inside the PABR. Optimization of operation pattern in PABR including switching manner and frequency depended on both the type of waste being treated and the flexibility of biomass to periodically changing micro-ecology conditions.